BORISENKO LYUDMILA ALEKSANDROVNA IS A WELL-KNOWN FOOD SCIENTIST AND A HIGHER SCHOOL WORKER - A. A. Bratsikhin (Современная наука и инновации)
Borisenko Lyudmila Aleksandrovna - Doctor of Technical Sciences, Professor celebrates her anniversary. She is the first graduate of the Department of Meat and Meat Products Technology of the Faculty of Food Production Technology of the Stavropol Polytechnic Institute (STPI), the first graduate in the history of StPI to receive a red diploma (1973), the first of the stream of graduate students of the Moscow Technological Institute of Meat and Dairy Industry and graduates of StPI to defend a thesis for the degree of Candidate of Technical Sciences (1977), as well as the first among the teachers of the department to defend a thesis for the degree of Doctor of Technical Sciences (2002). Science and pedagogical activity are always in the first place in her life. Under her leadership, 10 PhD theses have been defended, more than 400 scientific and educational works have been published. Her portfolio of inventions includes 20 copyright certificates and patents. Lyudmila Alexandrovna is an Honorary Worker of higher Professional Education of the Russian Federation, an Honorary Professor of SevKavSTU, a full member of the Russian Academy of Sciences, has been head of the Department of Commodity Science and Catering Technology for 7 years, has been a member of the Dissertation Council for 21 years D 212.245.05 and today continues her scientific activity at the Department of Food Technology and Engineering of NCFU.